Hostile space and female agency: Iphigenia in Iphigenia in Tauris and Helen in Helen of Euripides (Circe de clásicos y modernos, 2025)
The aim of this article is to analyze the relationship established between space and agency in two Euripidean “escape tragedies”, Helen and Iphigenia in Tauris. Approached from the two dimensions of its referents (Egypt and Tauris) and the stage of the theatrical performance, space is a fundamental element to analyze the agency developed by the protagonists throughout each play to escape from distant, exotic andbarbaric places that embody the otherness of Athenian society. We will focus on the different degree of confinement in which each character finds herself and the survival strategies carried out by them.
Keywords: Euripides; space; agency; Iphigenia in Tauris; Helen